2016
DOI: 10.1038/srep28699
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection mediated by inhibition of calpain during acute viral encephalitis

Abstract: Neurologic complications associated with viral encephalitis, including seizures and cognitive impairment, are a global health issue, especially in children. We previously showed that hippocampal injury during acute picornavirus infection in mice is associated with calpain activation and is the result of neuronal death triggered by brain-infiltrating inflammatory monocytes. We therefore hypothesized that treatment with a calpain inhibitor would protect neurons from immune-mediated bystander injury. C57BL/6J mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 78 publications
(110 reference statements)
1
26
0
Order By: Relevance
“…Additional studies of Howe et al (2012b) substantiated that neuronal loss during viral encephalitis is not primarily due to direct virus-mediated injury but much of the damage is associated with immune-mediated bystander pathology in response to infiltration of inflammatory monocytes/macrophages. Furthermore, the latter group showed that hippocampal neuron death in these animals is associated with calpain activation (Buenz et al, 2009), leading to the working model that infiltrating inflammatory cells release cytokines and other effector molecules that disrupt hippocampal circuitry, triggering seizures and inducing further disruption of the hippocampal network (Howe et al, 2016). Indeed, treatment with the calpain inhibitor ritonavir significantly reduced calpain activity in the hippocampus, protected hippocampal neurons from death, preserved cognitive performance, and suppressed seizure escalation in the Theiler' virus model (Howe et al, 2016).…”
Section: Brain Analysis Of Infiltrated Macrophages and Activated Micrmentioning
confidence: 99%
“…Additional studies of Howe et al (2012b) substantiated that neuronal loss during viral encephalitis is not primarily due to direct virus-mediated injury but much of the damage is associated with immune-mediated bystander pathology in response to infiltration of inflammatory monocytes/macrophages. Furthermore, the latter group showed that hippocampal neuron death in these animals is associated with calpain activation (Buenz et al, 2009), leading to the working model that infiltrating inflammatory cells release cytokines and other effector molecules that disrupt hippocampal circuitry, triggering seizures and inducing further disruption of the hippocampal network (Howe et al, 2016). Indeed, treatment with the calpain inhibitor ritonavir significantly reduced calpain activity in the hippocampus, protected hippocampal neurons from death, preserved cognitive performance, and suppressed seizure escalation in the Theiler' virus model (Howe et al, 2016).…”
Section: Brain Analysis Of Infiltrated Macrophages and Activated Micrmentioning
confidence: 99%
“…However, in contrast to serum, the brain levels rose again at 12 hpi and reached levels comparable to the 3 hpi values by 24 hpi. Based on our previous findings regarding the locus of neuronal injury during acute TMEV infection [7,22], we also measured CCL2 in microdissected hippocampus at the same timepoints in separate animals ( Figure 2C). CCL2 levels peaked at 6 hpi and were measured at 1500 pg per mouse (hippocampi pooled for each individual animal).…”
Section: Tmev Infection Induces Rapid Hippocampal Production and Relementioning
confidence: 99%
“…However, despite essentially complete resolution of the infection, permanent neurological sequelae such as impaired spatial learning [2,4], anxiety [5], and epilepsy [6] occur in most post-infectious animals. Uniquely, these neurologic problems largely stem from bystander loss of CA1 pyramidal neurons and subsequent disruption of hippocampal and hippocampal-cortical circuits [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…If our interpretation of these findings is correct, then post-ictal assessment of serum NSE may serve as a surrogate biomarker for measuring the efficacy of acute neuroprotective therapies aimed at preserving neurons in patients with epilepsy 34 . We recently reported that treatment of mice with an oral calpain inhibitor after the start of behavioral seizures induced by the neuroinflammatory response to acute viral infection resulted in preservation of hippocampal CA1 pyramidal neurons, preservation of cognitive performance, and abrogation of further seizure events 35 . Likewise, calpain inhibitor therapy started after onset of status epilepticus reduced seizure burden in the rat pilocarpine model 36 and preserved CA1 neurons in the kainic acid model 37 .…”
Section: Discussionmentioning
confidence: 99%